Production, Purification and Characterization of Cellulase from Cossus cossus Larvae - Baharuddin, Maswati (Al-Kimia, 2022)
This study aimed to purify and characterize the biochemical properties of cellulase from bacterial isolates of C. cossus larvae, to determine the effect of adding crude extract cellulase and pure enzymes to the hydrolysis of rice straw. The research steps included purification of enzymes by ion exchange chromatography and gel filtration chromotography, as well as SDS-PAGE electrophoresis analysis. Pure cellulases are characterized by their biochemical properties and applied in the hydrolysis of cellulose. The results showed that the characteristics of an optimum pH of 5.6, an optimum temperature of 70⁰C and a substrate concentration of 1.5% CMC, and a molecular weight of 36.49 kDa.